(untitled) (Huellas, 2020)
This research focuses on a section of the Alem Avenue axis in the city of Bahía Blanca, an intermediate urban center, where significant changes take place due to the interventions of the different participants involved. Along the process, changes at the morphological, functional, structural and symbolic levels are stated, which modify the materiality of the sector. In addition, the heritage perspective is included due to its importance in preserving the identity of the axis and the regulations restricting interventions and conflicts. Previous investigations from the Alem sector were also analyzed, but they presented unalike methodologies. For this reason, a new survey was carried out whose unit of analysis was the plot and its activity, many of which were new and non-existent in the current regulations for the sector. It was complemented with a review of materials in archives, map libraries, land registry, newspapers and periodicals. The information was processed with SIGArc Sig10 and QGis 2.18, apart from developing thematic cartography. The most interesting result was the importance and magnitude of residential use, due to the effect of densification. As regards the contribution itself, it implies the creation of a new base with a classification of the axis activities, and the characteristics of each plot, that enables the creation of a new instrument; namely, an interactive map.